ESSAYS ON THE THEORY OF DIRECTING. NEW METHODOLOGICAL AND SOCIO-CULTURAL ASPECTS OF THE UKRAINIAN SIXTIES - Коваленко, Елена (SWorldJournal, 2020)
The aim of the work is to develop a branch rare for the domestic scientific space - the theory of directing, tracking by scientific means the dynamics of internal changes in the individual style of the director, finding the most accurate tools of theater,